Ritual Architecture in Prehistoric Complex Hunter-Gatherer Communities: A Potential Example from Keatley Creek, on the Canadian Plateau. Issue 3 (20th July 2010) - Morin, Jesse
Abstract : A comparative analysis of housepit structures at the Keatley Creek site on the Canadian Plateau indicates that the ones on the periphery of the site cluster as a group, distinct from the domestic housepits in the core of the site. Comparison of the material attributes from a sample of peripheral structures with expectations of various nondomestic structures for the study region suggests that these structures were used as feasting or meeting-houses and not domestic residences. These peripheral structures originate during the Plateau horizon (2400–1200 B.P.) occupation of the site and were also used during the late Kamloops horizon (400–200 B.P.). It is argued here that understanding the history of these structures as loci of restricted ritual knowledge and training can contribute much to our interpretations of the bases and origins of social inequality in Keatley Creek, and other transegalitarian communities.